The Code-Switching on Facebook Profiles of Different Genders: The Case of Šalčininkai District - Miliun, Violeta (Taikomoji kalbotyra, 2020)
This study investigates functions of code-switching based on the model proposed by René Appel and Pieter Muysken. Code-switching is an interesting sociolinguistic phenomenon characteristic to bilingual and multilingual communities. It involves the use of different languages within the boundaries of a single sentence or between sentences in one specific domain or discourse. It is an individual language choice determined by such factors as the topic, the situation, the participants of a conversation, their interrelationship, emotions, and demonstration of one or more identities. On this basis, Appel and Muysken (2005) identified six functions of code-switching: referential, directive, expressive (related to identity), phatic (metaphorical), metalinguistic and poetic. This paper sets out to achieve several goals: (a) to find out which of these functions appear in the Facebook discourse of young people originated from Šalčininkai district, (b) to identify the main types of functions in girls’ and boys’ profiles, and (c) to study the frequency of the functions with regard to the variable of gender. The research material consists of 1 048 posts and comments published in 2017–2018 and obtained from 30 Facebook profiles. The dataset represents young people aged between 20 and 30 years, with Polish as their school language. Facebook posts and comments are investigated from a qualitative and quantitative perspective. The research results show that functionally code-switching is similar in both girls’ and boys’ Facebook discourse. On the profiles of both genders, the number of functions is identical, but the frequency of these functions varies. In the datasets of both genders, the most predominant function is directive, which appears when languages change depending on the language chosen by the interlocutor. This research could be informative for sociolinguists who investigate electronic discourse of young people from South East Lithuania and for those who focus on how environment influences the emergence of different linguistic codes on Facebook. The research could also stimulate greater interest of sociolinguists in the conversational features of residents in Šalčininkai district.